SiC crystal growth from the vapor and liquid phase - Hofmann, Heinz-Dieter; Bickermann, Matthias; Ebling, Dirk; Epelbaum, Boris; Kadinski, Lev; Selder, Markus; Straubinger, Thomas; Weingärtner, Roland; Wellmann, Peter; Winnacker, Albrecht (Materials Research Society Symposium - Proceedings, 2001)
The status of SiC vapor growth technique (PVT) is reviewed and related innovative aspects are introduced. Problems of the preparation of SiC crystals with uniform electronic properties are addressed, especially the growth of semiinsulating SiC. An overview about the performance of numerical modeling is given as tool for the optimization of the PVT process. Development activities in the field of liquid phase processing for the preparation of SiC bulk crystals and micropipe healing are presented. Finally recent results on the present understanding of filamentary void formation/elimination (micropipes, macrodefects) are summarize